XVI. International Conference on Logistics in Agriculture 2022: Conference Proceedings (University of Maribor Press, 2022)
16th International Conference on Agricultural Logistics organized by: Landscape Governance College GRM Novo mesto, Grm Novo mesto – center of Biotechnology and Tourism, the Faculty of Logistics of the University of Maribor, the Municipality of Sevnica and Cooperatice Union of Slovenia. The conference took place in cooperation with Faculty of Electrical Engineering and Computing and Institut of ‘Mihajlo Pupin’, University of Beograd. The central theme of this year’s conference will be “Digitalization of logistics in agriculture“. The conference has become traditional and paves the way for a different view of logistics in connection with agriculture.